Oesophageal cancer. Issue 10110 (25th November 2017) - Lagergren, Jesper; Smyth, Elizabeth; Cunningham, David; Lagergren, Pernilla
Summary: Oesophageal cancer is a clinically challenging disease that requires a multidisciplinary approach. Extensive treatment might be associated with a considerable decline in health-related quality of life and yet still a poor prognosis. In recent decades, prognosis has gradually improved in many countries. Endoscopic procedures have increasingly been used in the treatment of premalignant and early oesophageal tumours. Neoadjuvant therapy with chemotherapy or chemoradiotherapy has supplemented surgery as standard treatment of locally advanced oesophageal cancer. Surgery has become more standardised and centralised. Several therapeutic alternatives are available for palliative treatment. This Seminar aims to provide insights into the current clinical management, ongoing controversies, and future needs in oesophageal cancer.